2014
DOI: 10.1038/ncomms6239
|View full text |Cite
|
Sign up to set email alerts
|

Broad impacts of fine-scale dynamics on seascape structure from zooplankton to seabirds

Abstract: In marine ecosystems, like most natural systems, patchiness is the rule. A characteristic of pelagic ecosystems is that their ‘substrate’ consists of constantly moving water masses, where ocean surface turbulence creates ephemeral oases. Identifying where and when hotspots occur and how predators manage those vagaries in their preyscape is challenging because wide-ranging observations are lacking. Here we use a unique data set, gathering high-resolution and wide-range acoustic and GPS-tracking data. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 51 publications
4
83
0
Order By: Relevance
“…During a great part of the record (from ~1905 to 1970), there was an efficient upwelling of cold and nutrient‐rich waters probably in combination with a shallower thermocline and larger zooplankton; characteristics that are favorable for the development of anchovy (Bertrand et al., ). A shallow‐oxygenated habitat, promoted by the increase in upwelling, concentrates the prey near the surface enhancing anchovy foraging and leading to a reproductive advantage over sardine (Bertrand et al., , ). On the opposite, anchovy are less abundant when the productivity is very low (Figure g) and/or when the horizontal extent of the cold coastal waters is reduced and the oxycline deepen as was observed from the 1970s–mid‐1990s (Figure ; Bertrand et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…During a great part of the record (from ~1905 to 1970), there was an efficient upwelling of cold and nutrient‐rich waters probably in combination with a shallower thermocline and larger zooplankton; characteristics that are favorable for the development of anchovy (Bertrand et al., ). A shallow‐oxygenated habitat, promoted by the increase in upwelling, concentrates the prey near the surface enhancing anchovy foraging and leading to a reproductive advantage over sardine (Bertrand et al., , ). On the opposite, anchovy are less abundant when the productivity is very low (Figure g) and/or when the horizontal extent of the cold coastal waters is reduced and the oxycline deepen as was observed from the 1970s–mid‐1990s (Figure ; Bertrand et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Humboldt Current System, Bertrand et al . () showed that physical structures, such as internal waves, induce local deformations in the vertical location of the oxycline, where zooplankton, fish, Peruvian Boobies and Guanay Cormorants aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…, Bertrand et al. ). We hypothesize that the persistence of trophic hotspots in upwelling ecosystems is the result of physical forces that affect enrichment (nutrients and primary production), concentration, and retention of lower trophic levels (Bakun ).…”
Section: Introductionmentioning
confidence: 98%